The Influence of Singo Ulung Dance in the Celebration of Islamic Festivals - Hudaifah, Hudaifah; Rodiah, Ita (Universitas Islam Negeri Madura, 2023)
Singo Ulung is an art form originating from Bondowoso Regency, East Java Province, bordered to the west by Jember Regency, to the south by Situbondo Regency, and to the south by Banyuwangi Regency. The population of Bondowoso Regency is 776.252 citizens, and 90% of the population is Muslim. This research aims to discover the relationship between Singo Ulung Dance Art in celebrating the Islamic Festival and tohor related religious activities with Singo Ulung. The method used is descriptive qualitative, which uses observation, documentation, and interview techniques. The result of this research is Singo Ulung dance art, which is used to attract the community to carry out da'wah; performing Singo Ulung dance can attract the community to enliven the celebration of Islamic festivals and other religious activities.